2015
DOI: 10.1111/1440-1681.12433
|View full text |Cite
|
Sign up to set email alerts
|

Honey feeding protects kidney against cisplatin nephrotoxicity through suppression of inflammation

Abstract: Cisplatin is a highly effective chemotherapeutic drug used to treat a wide variety of solid tumors. However, its use was limited due its dose limiting toxicity to the kidney. Currently, there are no therapies available to treat or prevent cisplatin nephrotoxicity. Honey is a naturally occurring complex liquid and widely used in traditional Ayurvedic medicine to treat many illnesses. However, its effect on cisplatin nephrotoxicity is unknown. To determine the role of honey in cisplatin nephrotoxicity, animals w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 25 publications
(34 reference statements)
2
20
0
Order By: Relevance
“…In addition, it was demonstrated that honey collected in the United Arab Emirates can protect liver and kidney during acute blood loss, food restriction, and after carbon tetrachloride intoxication [ 10 - 14 ]. Other studies found that honey from different regions showed a protective effect in cisplatin, carbon tetrachloride, and cyclophosphamide-induced kidney toxicity [ 15 - 17 ]. Honey treatment improved the kidney function, increased antioxidant enzymes, and decreased lipid peroxide levels and improved the morphology of the kidney cells of the melamine-fed rats [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was demonstrated that honey collected in the United Arab Emirates can protect liver and kidney during acute blood loss, food restriction, and after carbon tetrachloride intoxication [ 10 - 14 ]. Other studies found that honey from different regions showed a protective effect in cisplatin, carbon tetrachloride, and cyclophosphamide-induced kidney toxicity [ 15 - 17 ]. Honey treatment improved the kidney function, increased antioxidant enzymes, and decreased lipid peroxide levels and improved the morphology of the kidney cells of the melamine-fed rats [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although the exact mechanism responsible for cisplatin-induced nephrotoxicity is not fully understood, there is growing evidence that multiple cellular and molecular mechanisms were found to be involved [ 3 ]. The generation of reactive oxygen species (ROS) and decrease of antioxidant enzymes was found to be involved [ 4 , 5 ]. Excessive ROS generation caused by cisplatin may lead to lipid peroxidation (LPO) and delayed-onset kidney injury.…”
Section: Introductionmentioning
confidence: 99%
“…10,16 It has been reported that inhibition of NFκB signaling has protective effects on cisplatin nephropathy. [20][21][22][23][24] Our data indicated that DS-5272 inhibits NFκB signaling, which contributes to amelioration of cisplatin nephropathy in vivo and decreased cell injury in vitro. In this study, however, there were two major discrepancies between the time course of MDM2 expression and the effect of DS-5272.…”
Section: Discussionmentioning
confidence: 65%